Experimental study of fire damage to reinforced concrete tunnel slabs. (January 2022) - Hua, Nan; Elhami Khorasani, Negar; Tessari, Anthony; Ranade, Ravi
Abstract: Fire hazards are a major threat to tunnel structures; however, the existing understanding of the behavior of tunnel linings under fire is limited, which restricts cost-effective and safe design of tunnels for fire. The research work in this paper aims to experimentally evaluate and quantify fire damage to tunnel linings considering a combination of influencing factors. The effects of three parameters on fire damage to the ceiling (typically the most damaged area) of a tunnel lining are studied through five furnace tests on large-scale reinforced concrete slabs. The parameters include: (1) concrete composition - presence/absence of polypropylene fibers, (2) the level of structural restraint (induced using post-tensioned strands), and (3) the fire intensity and duration. These parameters are selected to reflect realistic scenarios and provide a rational basis for evaluating tunnel damage, in terms of crack pattern, spalling, discoloration, non-destructive testing, and deflections during fire and after cooling. This research provides vital experimental data for fire damage assessment of reinforced concrete tunnel linings, and assists in verifying numerical models for analyzing structural performance during both the heating and cooling phases of fire. Highlights: A total of five fire tests on large-scale reinforced tunnel concrete slabs are conducted. The considered test parameters are concrete composition, level of restraint, fire intensity, and fire duration. Fire damage to the slabs is evaluated from multiple aspects. The lack of active or passive fire protection may lead to irrecoverable damage under moderate railway tunnel fires. Moderate railway tunnel fires result in an average reduction of 15–20% in concrete strength.